Axial Compression Properties of Special-Shaped 3D Tubular Woven Composites. Issue 2 (March 2021) - Wang, Jingjing; Lyu, Lihua; Guo, Jing; Xiong, Xiaoqing; Wang, Ying; Ye, Fang
Axial compression properties of special-shaped 3D tubular woven composites with basalt fiber filament tows were studied. Special-shaped 3D tubular woven fabrics composites with three different thicknesses were woven on an ordinary loom and fabricated by the vacuum assisted resin transfer molding (VARTM) process. Load-displacement and energy-displacement curves were obtained from experimental tests. Results showed that for special-shaped 3D tubular woven composites, the load and energy absorption were greater with thickness and the compression property improved. Through the analysis of the mathematical equation and correlation coefficient of the load-displacement and energy-displacement relation, the fitting effect of the curves were good. The mathematical equation of the method could be used to simplify the functional relationship between load, energy, and displacement.